2023
DOI: 10.2174/1381612829666230524153002
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Application of Chitosan and Chitosan Derivatives: A Comprehensive Review

Yash Kankariya,
Bappaditya Chatterjee

Abstract: Chitosan (CS) is a widely known naturally occurring polysaccharide made of chitin. The Low solubility of chitosan in water restricts its use in medical applications. However, several chemical modifications have made chitosan superior in solubility, biocompatibility, biodegradability, stability, and easy functionalization ability. All these favourable properties have increased chitosan’s application in drug delivery and biomedical fields. Chitosan-based nanoparticles or biodegradable controlled-release systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…This type of biopolymer has important applications in tissue regeneration, drug delivery, biofuels, and the food industry [ 31 , 32 ]. Additionally, research has also found that phosphorylated chitosan can be synthesized by grafting by reacting mono(2-methacryloyloxyethyl) phosphate with chitosan, which advantageously imparts amphiphilic properties to the chitosan and increases its antimicrobial activity [ 62 , 63 ].…”
Section: Chitosan and Chitosan Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of biopolymer has important applications in tissue regeneration, drug delivery, biofuels, and the food industry [ 31 , 32 ]. Additionally, research has also found that phosphorylated chitosan can be synthesized by grafting by reacting mono(2-methacryloyloxyethyl) phosphate with chitosan, which advantageously imparts amphiphilic properties to the chitosan and increases its antimicrobial activity [ 62 , 63 ].…”
Section: Chitosan and Chitosan Modificationmentioning
confidence: 99%
“…In addition to the reactions mentioned above, commonly used chemical modifications of chitosan include glycosylation, sulfation, etherification, thiolation, etc. [ 62 , 63 , 64 , 65 ]. Research has shown that a chitosan Schiff base containing thiophene, indole, and pyrazole groups and CS was transformed into nanoparticles with high inhibitory activity on tumor cells [ 66 ].…”
Section: Chitosan and Chitosan Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan and its derivatives have sustained considerable interest for several decades due to its diverse properties that hold significance for medical applications [ 31 , 32 , 33 , 34 ]. Chitosan is actively utilized in the development of medical products, including wound dressings [ 35 , 36 ] and burn wound treatments [ 37 , 38 ], dental compositions [ 39 ], drug delivery systems [ 40 , 41 ], dietary supplements [ 42 ], and various other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (CTS) is a type of polysaccharide obtained through the deacetylation of chitin. Due to its exceptional film-forming ability, adsorption, biocompatibility, and porous structure, it is widely used in the preparation of electrochemically modified electrodes [30,31]. Moreover, the CTS molecular chain contains -NH 2 and -OH groups that exhibit strong chelation ability for heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%